2016
DOI: 10.1007/s00198-016-3598-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y mediates glucocorticoid-induced osteoporosis and marrow adiposity in mice

Abstract: NPY mediates the glucocorticoid-induced disturbance of mineral accretion and marrow adipogenesis through post-translational modification of PPARγ. This study brings a new molecular insight into the disintegration of adipogenic and osteogenic activities within glucocorticoid-mediated osteoporotic skeletons. Control of NPY is an alternative strategy to ameliorate glucocorticoid-induced bone destruction and fatty marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…For example, therapies involving intermittent PTH, (22,24) sost-antibody, (18) anti-Rankl antibody, (19) IL-6 neutralizing antibody, (25) as well as inhibition of HSP90 (26) and endoplasmic reticulum stress (23) prevented the bone phenotypes due to GC treatment to variable degrees in vivo. Moreover, genetic approaches using knockout mice of mitogen-activated protein kinase phosphatase 1, (27) plasminogen activator inhibitor 1, (28) Npy, (29) sost, (14) and autophagy-related gene 7 (30) have been used to prevent GC-induced bone loss but resulted in variable outcomes. Our transgenic (TG) mice that overexpress human WNT16 in bone tissue displayed significantly higher bone mineral density in whole body, hip, and spine.…”
Section: Discussionmentioning
confidence: 99%
“…For example, therapies involving intermittent PTH, (22,24) sost-antibody, (18) anti-Rankl antibody, (19) IL-6 neutralizing antibody, (25) as well as inhibition of HSP90 (26) and endoplasmic reticulum stress (23) prevented the bone phenotypes due to GC treatment to variable degrees in vivo. Moreover, genetic approaches using knockout mice of mitogen-activated protein kinase phosphatase 1, (27) plasminogen activator inhibitor 1, (28) Npy, (29) sost, (14) and autophagy-related gene 7 (30) have been used to prevent GC-induced bone loss but resulted in variable outcomes. Our transgenic (TG) mice that overexpress human WNT16 in bone tissue displayed significantly higher bone mineral density in whole body, hip, and spine.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive use of glucocorticoids damaged the function of bone cells [4,6], and the NPY system was found to play a negative role in the regulation of bone remodeling and osteoblast activity [9,12,17,25]. A recent study has suggested that NPY signaling mediated glucocorticoid-induced osteoporosis in mice [20]. The Y1 receptor, one of the most important receptors for NPY, was expressed in osteoblasts and participated in the regulation of bone metabolism [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study demonstrated that increased NPY expression was associated with glucocorticoid-induced bone loss and marrow adiposity in mice, whereas NPY deletion protected bone tissue against glucocorticoid-induced deterioration [20]. The Y1 receptor is the main receptor for NPY; however, its role in the glucocorticoid-induced suppression of osteoblast differentiation at the cell level has not yet been defined.…”
Section: Introductionmentioning
confidence: 99%
“…GC are known to inhibit bone formation and high levels of GC in human (Cushing syndrome) are associated with increased risk of fractures and increased MAT formation. GC stimulates the synthesis of collagenase III, which is an enzyme involved in bone matrix degradation, inhibits the anabolic effect of IGF hormones and induces significant changes in neuropeptide Y that may contribute to osteoporosis and increased MAT phenotype (76). Life-course timepoint analysis has shown that circulating GC follow an age-related trajectory, which can be affected by both the external environment and internal physiological events, which varies between gender and individuals (77).…”
Section: Glucocorticoids (Gc)mentioning
confidence: 99%